Local-Level Immigration and Life Satisfaction: The EU Enlargement Experience in England and Wales - Artjoms Ivlevs; Michail Veliziotis (Institute for the Study of Labor (IZA), 2015)
The 2004 European Union enlargement resulted in an unprecedented wave of 1.5 million workers relocating from Eastern Europe to the UK. We study how this migrant inflow affected life satisfaction of native residents in England and Wales. Combining the British Household Panel Survey with the Local Authority level administrative data from the Worker Registration Scheme, we find that higher local level immigration increased life satisfaction of young people and decreased life satisfaction of old people. This finding is driven by the initial 'migration shock' – inflows that occurred in the first two years after the enlargement. Looking at different life domains, we also find some evidence that, irrespective of age, higher local level immigration increased natives' satisfaction with their dwelling, partner and social life.
Keywords: F22; J15; I31; 330; immigration; life satisfaction; United Kingdom; 2004 EU enlargement